Asset Pricing without Garbage - Tim Alexander Kroencke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper provides an explanation why garbage as a measure of consumption implies a several times lower coefficient of relative risk aversion in the consumption-based asset pricing model than consumption based on the official National Income and Product Accounts (NIPA): Unlike garbage, NIPA consumption is filtered to mitigate measurement error. I apply a structural model of the filtering process, which allows to revoke the filter inherent in NIPA consumption. Unfiltered NIPA consumption performs as well as garbage in explaining the equity premium and risk-free rate puzzle. Furthermore, I find that two other popular NIPA-based measures, three-year and fourth-quarter NIPA consumption, are related to unfiltered NIPA consumption. Both can be viewed as ad hoc unfilter rules.
Keywords: G12; E21; E44; 330